AN ANALYSIS OF STUDENTS’ ABILITY IN CONSTRUCTING SIMPLE PRESENT TENSE SENTENCES (A CASE STUDY AT THE STATE JUNIOR HIGH SCHOOL (SMP NEGERI 2) HAMPARAN PERAK) - Yuliana Ningsih (Jurnal Humaniora Teknologi, 2016)
The research deals with students’ ability in constructing Simple Present Tense and it is objected to see whether the students are able to use Simple Present Tense.This research was conducted at the third grade of State Junior High School (SMPN 2) Hamparan Perak Kabupaten Deli Serdang. From 60 students of the total sample were selected randomly. The data was obtained by administering a test related to Simple Present Tense. This study was conducted in quantitative approach with the standard ability for an individual mastery of learning is minimum 70% of the test given and that is suggested by Tinambunan (1980) which is divided in to five levels of ability namely: out standing ability (A), above ability (B), average ability (C), below average ability (D), and insufficient ability (E) with each level represents different percentage.The population of this research was the third year students of SMPN 2 Hamparan Perak Kabupaten Deli Serdang. The total number of the population was 119 students. There are three classes; III.1, III.2, and III.3. The researcher used simple random sampling to select the sample.The result shows that the students’ ability in constructing Simple Present Tense is very low as there was no student in the levels out standing ability, above average ability, and average ability. There were 6 students in the level of below average ability (10%) and 54 students in the level of insufficient ability (90%).